REACTIVE POWER COMPENSATION AND ENERGY WASTE REDUCTION DURING START-UP OF THE ELECTRIC MOTOR OF UXK COTTON CLEANING DEVICE - Obidov, Avazbek; Akhmadalieva, Dilnoza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Increasing production capacity in the cotton primary processing industry by energy-efficient methods and the rapid introduction of automation methods in the cotton industry have increased the demand for better process control. This has led to many new applications for the variable speed drive inverter to control the speed and torque of driven machinery. Variable speed inverter drives are also used to meet specific starting and stopping requirements.